KONSEP KHILAFAH MENURUT AR-RANIRY DAN SYIAH KUALA: (Suatu Analisis Diskriptis) - Ahmad Syarbaini (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Islamization Aceh is done directly by the preacher (missionaries) of Islam of the Arab. Pengislaman Aceh by the Arab nations did not have implications on the cultural Arabization Aceh. Acehnese culture develops based on the jurisprudence of Aceh (local wisdom), especially in the 17th century AD It is identified based on the legal principle established by ar-Raniry and Syiah Kuala basic thinking about the legal permissibility of Acehnese women's role in public life. The legal principle is built on the concept of